2017
DOI: 10.5194/acp-17-11491-2017
|View full text |Cite
|
Sign up to set email alerts
|

Sources of non-fossil-fuel emissions in carbonaceous aerosols during early winter in Chinese cities

Abstract: Abstract. China experiences frequent and severe haze outbreaks from the beginning of winter. Carbonaceous aerosols are regarded as an essential factor in controlling the formation and evolution of haze episodes. To elucidate the carbon sources of air pollution, source apportionment was conducted using radiocarbon ( 14 C) and unique molecular organic tracers. Daily 24 h PM 2.5 samples were collected continuously from October 2013 to November 2013 in 10 Chinese cities. The 14 C results indicated that non-fossil-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 59 publications
5
27
0
Order By: Relevance
“…eBC enhancement along with air qual-ity deterioration has also been reported elsewhere (Q. Liu et al, 2016;. At LH and HA, the enhancement of the eBC level from clean to polluted periods was due to both elevated BC emissions from biomass burning (BC bb ) and fossil fuel combustion (BC ff ) (Fig.…”
Section: Clean Days Vs Pollution Episodessupporting
confidence: 77%
“…eBC enhancement along with air qual-ity deterioration has also been reported elsewhere (Q. Liu et al, 2016;. At LH and HA, the enhancement of the eBC level from clean to polluted periods was due to both elevated BC emissions from biomass burning (BC bb ) and fossil fuel combustion (BC ff ) (Fig.…”
Section: Clean Days Vs Pollution Episodessupporting
confidence: 77%
“…For example, Zhang et al (2015a) found that 48 ± 9 % total carbonaceous aerosols were contributed by non-fossil sources in urban areas of four large Chinese cities in the winter of 2013. 14 C measurements conducted in early winter in 10 Chinese cities show that, on average, 65 ± 7 % total carbonaceous aerosols were derived from non-fossil sources (Liu et al, 2017). When 14 C analysis is conducted for OC and EC separately, contributions from biomass burning and other non-fossil sources to carbonaceous aerosols can be separated for a more comprehensive source apportionment.…”
mentioning
confidence: 99%
“…Fossil WSOC (WSOC fossil ) therefore is thought to be a good proxy of fossil SOC (SOC fossil ). 14 C analysis of WIOC and WSOC can thus provide new insights into sources and formation processes of primary and secondary OC, respectively, and has been applied in several source apportionment studies (e.g., Liu et al, 2016a, b;Dusek et al, 2017;Liu et al, 2017). For example, using this approach, Y. L. Zhang et al (2014) found that secondary fossil OC dominates total fossil OC in a background site in southern China.…”
mentioning
confidence: 99%
“…For example, Zhang et al (2015b) found that 48 ± 9% total carbonaceous aerosols were contributed by non-fossil sources in urban areas of 4 large Chinese cities in winter of 2013. 14 C measurements conducted in early winter in 10 Chinese cities show that on average 65 ± 7% total carbonaceous aerosols were derived from non-fossil sources (Liu et al, 2017). When 14 C analysis is conducted for OC and EC separately, contributions from biomass burning and other non-fossil sources to carbonaceous aerosols can be separated 25 for a more comprehensive source apportionment.…”
Section: Introductionmentioning
confidence: 99%
“…(WSOCfossil) therefore is thought to be a good proxy of fossil SOC (SOCfossil). 14 C analysis of WIOC and WSOC can therefore provide new insights into sources and formation processes of primary and secondary OC, respectively, and has been applied in several source apportionment studies (e.g., Liu et al, 2016aLiu et al, , 2016bDusek et al, 2017;Liu et al, 2017). For example, using this approach, Y. L. found that secondary fossil OC dominates total fossil OC in a background site in southern China.…”
Section: Introductionmentioning
confidence: 99%